Cultivation of Melia dubia Cav.– A fast growing native tree species and constraints faced by the farmers’ in western region of Tamil Nadu - Saravanan, S. (Indian Journal of Agroforestry, 2020)
The present study was conducted in Erode and Coimbatore districts of Tamil Nadu, to find out the problems faced by the Melia dubia Cav. tree growers in adoption of new indigenous fast growing species in farm land condition as a block plantation as well as in the form of agroforestry systems. The data were collected from 120 Melia growers through structured questionnaire method. It was found that the recommended practices either did not reach the farming communities or were not practiced by them. Most of the farmers do not purchase quality planting material. Melia growers were needed to be addressed and convinced about the usefulness of these silvicultural practices for better growth condition and higher economic returns. Being a new tree species introduced among the farming community, the cultivation techniques were to be brought out in local language for better understanding of the farmer’s. The major problems faced by the farming community were non-availability of quality planting materials, high cost for seedling from private nursery, pest and disease management, marketing, non-availability of loan or credit facilities, tree insurance and tree cultivation techniques. Melia plantation is generally not adopted by the farmer’s due to the non-availability of technical inputs and proper extension strategies.